(untitled) (CIPEEX, 2022)
THE NATIONAL POLICY ON PRIMARY CARE HAS AS ITS PRIMARY OBJECTIVE THE ESTABLISHMENT OF NORMS AND GUIDELINES FOR THE ORGANIZATION OF BASIC HEALTH CARE IN THE UNIFIED HEALTH SYSTEM. THE IMPLEMENTATION OF THIS POLICY IS DONE BY THE SUM OF EFFORTS OF SOCIAL MOVEMENTS, POPULATION, WORKERS AND MANAGERS OF THE SPHERES OF FEDERAL, STATE AND MUNICIPAL GOVERNMENT, FOCUSING ON THE INTEGRAL CARE CENTERED ON THE PERSON, THUS DELEGATING THE HEALTH NEEDS OF THE POPULATION. PRIMARY CARE IS THE FIRST POINT OF CONTACT AND THE PREFERENTIAL ENTRANCE DOOR OF THE UNIFIED HEALTH SYSTEM (SUS), THIS CHARACTERISTIC MAKES IT AN ENRICHING PROCESS AND STIMULATES THE RECOGNITION OF LOCOREGIONAL SPECIFICITIES, THE DYNAMICITY OF THE TERRITORY, AND THE HEALTH DETERMINANTS WHICH CHARACTERIZES A CERTAIN SOCIAL GROUP AND GEOGRAPHIC REGION. THE SOCIOCULTURAL ASPECT CONFERS THE HOLISTIC ATTENTION PROMOTING ACTIONS OF HEALTH SURVEILLANCE BY AGREEING ON A CONTINUOUS PROCESS OF OBSERVATION OF THE REALITY, DATA COLLECTION FOCUSED ON HEALTH AND INSTITUTIONALIZATION OF PUBLIC HEALTH POLICIES AIMED AT PREVENTION, PROTECTION AND HEALTH PROMOTION OF THE POPULATION. THIS PAPER AIMS TO REPORT ON HOW PNAB STIMULATES EQUAL ACCESS AMONG SUS USERS AND HOW IT IS POSSIBLE TO STIMULATE THE INCLUSION AND ACCESSIBILITY OF NEW PATIENTS IN THIS COMPREHENSIVE PUBLIC HEALTH SYSTEM, REAFFIRMING THE IDEAL OF HEALTH PROMOTION. FINALLY, IT IS UNDERSTOOD THAT THE TEAMS THAT DEVELOP HEALTH WORK IN THE UBS, CARRY OUT SERVICES CONSIDERING THE NEEDS OF THE POPULATION, BEING DEFINED BY THE GEOGRAPHICAL LOCATION THAT IT IS. KEYWORDS: SINGLE HEALTH SYSTEM; INCLUSION; ACCESSIBILITY; PRIMARY CARE.